(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
PhytoSpherix™ is a nanoparticle derived from non-genetically modified sweet corn, isolated from the plant, and Actigym™ is a marine ingredient created by a Bermudan bacterium (a Bacillus sp.). Therefore, our objectives were to (i) formulate an emulsion containing PhytoSpherix™ and Actigym™ marine ingredients, (ii) stabilize the emulsion with Sustoleo™ MCT and SustOleo™ GMS, (iii) determine the sun protection factor (SPF), (iv) analyze ultraviolet A/ultraviolet B (UVA/UVB) protection, and (v) assess in vivo skin melanin, erythema, elasticity, and moisture content. Materials and Methods: A new oil-in-water emulsion was prepared, incorporating PhytoSpherix™ and Actigym™ marine ingredient, using a mixture of cetyl alcohol, hydrogenated rapeseed oil, triheptanoin, glyceryl stearate, and distilled water. Various tests were conducted, including accelerated thermal stability, pH measurement, color, smell, phase separation, liquefaction, rheology, SPF, UVA/UVB protection, irritation, and in vivo effects on skin (melanin, erythema, elasticity, hydration, image visualization, and sensory evaluations). Results: The emulsion demonstrated excellent stability in both short and long-term testing, maintained a pH of 5.81, showed no phase separation, and had a viscosity of 1.042 Pa.s with a pseudoplastic trend, indicating shear-thinning behavior. It exhibited satisfactory safety profiles, causing no irritation in rats or human volunteers. In vitro testing revealed a SPF value of 23.70 and a UVA/UVB ratio of 0.51, providing effective UVB protection. Furthermore, it improved skin elasticity and moisture retention while reducing melanin and erythema compared to the control. Conclusion: The newly formulated emulsion was deemed stable and showed promising effects against UV radiation on the skin, warranting further investigation.